2014
DOI: 10.1521/psyc.2014.77.3.247
|View full text |Cite
|
Sign up to set email alerts
|

Interpersonal Change Following Intensive Inpatient Treatment

Abstract: Objective: Persons admitted for inpatient psychiatric care often present with interpersonal difficulties that disrupt adaptive social relations and complicate the provision of treatment. Whereas domains of psychosocial functioning in this population demonstrate clear growth in response to intervention, the impact of treatment on more complex patterns of interpersonal behavior has been largely overlooked within the existing literature. Interpersonal profiles characteristic of psychiatric inpatients were identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…One study reported IIP quadrant data (Puschner et al 2004) for treatment with either PD, CBT or PP. In the PD group only, the fastest rate of improvement was found for participants with problems in the hostile-submissive quadrant, and the slowest rate of improvement was found for participants with problems in the friendly-dominant quadrant, of the IIP-C. One additional study (Clapp et al 2014), in which the researchers had had determined their own study-specific IIP-C profiles, reported that 48% of participants with a pre-treatment submissive profile (elevations across the non-assertive, overly accommodating, and self-sacrificing scales) had transitioned to a normative profile at the end of treatment, compared with 57.1% of those with a hostile/withdrawn profile (elevations across the vindictive/self-centred, cold/distant, and socially inhibited subscales).…”
Section: Pre-treatment Iip Data and Outcomementioning
confidence: 94%
“…One study reported IIP quadrant data (Puschner et al 2004) for treatment with either PD, CBT or PP. In the PD group only, the fastest rate of improvement was found for participants with problems in the hostile-submissive quadrant, and the slowest rate of improvement was found for participants with problems in the friendly-dominant quadrant, of the IIP-C. One additional study (Clapp et al 2014), in which the researchers had had determined their own study-specific IIP-C profiles, reported that 48% of participants with a pre-treatment submissive profile (elevations across the non-assertive, overly accommodating, and self-sacrificing scales) had transitioned to a normative profile at the end of treatment, compared with 57.1% of those with a hostile/withdrawn profile (elevations across the vindictive/self-centred, cold/distant, and socially inhibited subscales).…”
Section: Pre-treatment Iip Data and Outcomementioning
confidence: 94%